2014
DOI: 10.1038/srep05113
|View full text |Cite
|
Sign up to set email alerts
|

Minimally destructive sampling of type specimens of Pyropia (Bangiales, Rhodophyta) recovers complete plastid and mitochondrial genomes

Abstract: Plant species, including algae and fungi, are based on type specimens to which the name of a taxon is permanently attached. Applying a scientific name to any specimen therefore requires demonstrating correspondence between the type and that specimen. Traditionally, identifications are based on morpho-anatomical characters, but recently systematists are using DNA sequence data. These studies are flawed if the DNA is isolated from misidentified modern specimens. We propose a genome-based solution. Using 4 × 4 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 43 publications
1
54
0
Order By: Relevance
“…The intraspecific organellar genome variation exhibited between specimens of C. sungminbooi from Denmark and California, USA are similar to those reported for Pyropia perforata (J. Agardh) S.C.Lindstrom (Hughey et al 2014). They found that the lectotype of P. perforata from San Francisco, California differed from a specimen from La Jolla, California by 185 SNPs and 14 gaps, and another from San Juan Island, Washington by 75 SNPs and one gap for its plastid genome.…”
Section: Nadh Dehydrogenasesupporting
confidence: 63%
See 1 more Smart Citation
“…The intraspecific organellar genome variation exhibited between specimens of C. sungminbooi from Denmark and California, USA are similar to those reported for Pyropia perforata (J. Agardh) S.C.Lindstrom (Hughey et al 2014). They found that the lectotype of P. perforata from San Francisco, California differed from a specimen from La Jolla, California by 185 SNPs and 14 gaps, and another from San Juan Island, Washington by 75 SNPs and one gap for its plastid genome.…”
Section: Nadh Dehydrogenasesupporting
confidence: 63%
“…The genome libraries were constructed using the methods outlined by Hughey et al (2014). The DNA library was sequenced using Illumina (Illumina Inc., San Diego, CA, USA) 36 bp paired-end analysis with the manufacturer's protocol via the cBot and HiSeq 2000 by HTGC (http:// www.htseq.org/).…”
Section: Plastid Genome Sequencing Assembly Annotationmentioning
confidence: 99%
“…The genome library was constructed using the methods outlined by Hughey et al (2014) and analyzed using Illumina 36 bp paired-end sequencing following the protocol of the manufacturer via the cBot and HiSeq 2000 by HTGC (http://www.htseq.org/). The reads were base called with Illumina's standard pipeline yielding 356 filtered reads of 11 483 length.…”
Section: Methodsmentioning
confidence: 99%
“…The genomic library was constructed and sequenced by the High-Throughput Genomics Center (Seattle, Washington). The data were assembled using Velvet 1.2.08 (Zerbino & Birney 2008) on the Bio-Linux platform (Field et al 2006) using the assembly and annotation methods described by Hughey et al (2014). Alignment of the Florideophyte mitogenomes was completed using default settings in MAFFT (Katoh & Standley 2013).…”
mentioning
confidence: 99%